Post 2015: the need for an enabling global economic governance framework - Kathrin Berensmann; Axel Berger; Clara Brandi (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
In September 2015, the United Nations (UN) adopted a new global development framework, the “2030 Agenda for Sustainable Development”, which includes the Sustainable Development Goals (SDGs). The SDGs thereby replace the Millennium Development Goals (MDGs), which were supposed to be realized by the end of 2015. What is the role of global economic governance in the 2030 Agenda, and specifically in the SDGs? The MDGs failed to adequately address issues of global economic governance. MDG 8, which was intended to develop a global partnership for development by 2015, did not create a more effective and fairer framework to enable countries to promote human development within the global economy. What is more, since the MDGs were adopted, broader economic globalization, with more interdependence between countries and shifting economic dynamisms, has changed the world economy. The past two decades have witnessed the quadrupling of global trade and a tenfold increase in South-South trade. In the same period, emerging economies' share in global foreign direct investment (FDI) increased from just 5 per cent to over 30 per cent. Similarly, financial flows have not just swollen during the past two decades, they have also switched direction, with financial surpluses from emerging economies flowing `uphill' in order to cover current account deficits in advanced countries. In a decade's time, inter-national cooperation has been transformed from the dichotomy of the `rich North'/`poor South' to new forms of international economic cooperation created by new actors. In light of these new circumstances, the SDGs should place more emphasis on global economic governance issues – some of which are not at all or only inadequately addressed. Whilst the 2030 Agenda for Sustainable Development does more to address global economic governance issues, it exhibits significant lacks. Key global economic challenges remain inadequately addressed: Greater adjustments to the international trading system are needed to ensure that trade and foreign investment support sustainable development. More must be done to increase developing countries' access to global value chains, reduce their trade costs and reform the multilateral trading system, especially against the background of `mega-regional' trade agreements. The rules and institutions of global finance must be reformed to guarantee greater financial stability and improve global cooperation with respect to the fight against illicit financial flows and transfers. The global financial safety net and the global debt governance system remain incomplete.
Keywords: 330; Handel und Investitionen; Internationales Finanzsystem